Students’ Perceptions of English Medium Instruction (EMI) in Secondary School Bilingual Classes: A Case Study - Kurniati, Maida (Universitas Pendidikan Indonesia, 2023)
In contemporary international secondary education in Indonesia, English-Medium Instruction (EMI) has gained popularity and expanded into a rising global phenomenon. Recognizing this phenomenon and the importance of English language skills for students from an early age, this study aims to investigate the perceptions of junior high school students in bilingual classes on the use of EMI in schools. A qualitative research design in the form of a case study was adopted in this study. It involved thirteen (13) junior high school students (2 males, 11 females) of two bilingual class programs at a private junior high school in Bandung, West Java, Indonesia. Data were collected through questionnaires, semi-structured interviews, and an FGD (forum group discussion) session. The findings indicate that all participants show positive perceptions of the EMI implementation in terms of the importance of EMI for Learning, the importance of EMI for career, and the use of EMI associated with the preservation of tradition issue. This study also reveals the obstacles that are often faced in the use of EMI such as a lack of understanding of technical terms in the content course and teachers' low proficiency in English. Therefore, it is expected that this study will offer recommendations from the perspectives of EFL practitioners in order to optimize the advantages of the EMI policy in an EFL context.